DISTRIBUSI DIATOM EPIFITIK SECARA VERTIKAL PADA BATANG Avicennia sp DI KAWASAN MUARA SEI UNDAN KABUPATEN INDRAGIRI HILIR - Susiyanti. N; Sofyan Husein Siregar; Irvina Nurrachmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This research was conducted from April-Mei 2013 in the Waters around the Estuary Sei Undan, Kabupaten Indragiri Hilir, Riau Province. The aim of this research is to understand the distribution and abundance of epiphytic diatom presenting on the trunk of the Avicennia sp which is related to water quality factor. Survey method was applied on this research where data were obtained by direct observation in the field. The samples of epiphytic diatom were analyzed in the Laboratory of Marine Biology. Water quality parameters were measured in situ.Six species of epiphytic diatom were found on the trunk. The abundance of epiphytic diatom on the trunk ranged from 0 to 9.59 ind/cm2. Beside that, water quality parameters were in the sufficient range for marine epiphytic diatom.Keywords: epiphytic, diatom, avicennia sp, Sei Undan